“The family farms together, the decisions, however are made by the man” —Matrilineal land tenure systems, welfare and decision making in rural Malawi - Djurfeldt, Agnes Andersson; Hillbom, Ellen; Mulwafu, Wapulumuka O.; Mvula, Peter; Djurfeldt, Göran (Land use policy, 2018)
Improved female control over land is often put forth as a means of raising the productivity of smallholder agriculture, enhancing female bargaining power and raising women’s incomes. The article uses some quantitative but primarily qualitative data on access to income and decision making, to analyse gender patterns related to welfare, incomes and control over resources in a context where women’s rights to land are particularly strong, that is in a matrilineal and uxorilocal setting. Women’s land rights are contextualized in relation to labour intensive, low productive smallholder systems and the paper assesses to what extent female control over land affects welfare outcomes, decision making and intra-household control over incomes and labour. While we find that female control over land does affect intra household relations it is clear that land reform is not enough to ensure gender equality. For any land use policy reform to have a profound affect it would have to also take into account control over other productive resources, e.g. labour, as well as the wider institutional and political context.